Participatory Methodologies with Victims: An Emancipatory Approach to Transitional Justice Research. Issue 2 (29th May 2015) - Robins, Simon; Wilson, Erik
Abstract: Transitional justice seeks to address legacies of violence around political transition from authoritarianism and armed conflict. It does so in ways driven by a global discourse that is prescriptive and often remote from the contexts in which it is articulated and the populations it claims to serve. Transitional justice is also embedded in teleological liberal approaches to transition, with a perceived endpoint of liberal democracy. Critical approaches to transitional justice have used qualitative methodologies to understand the agendas of those—notably victims of violence—that transitional justice foregrounds, and to demonstrate that transitional justice mechanisms often serve elite agendas, while minimizing the agency of socially excluded populations. An alternative, minimally explored route to victim engagement with such processes has been the mobilization of victims and victim organizations, an emancipatory approach that seeks to provide a space for victims to engage in transitional justice debates on their own terms. Here, a research engagement with a victims' organization through a Participatory Action Research modality is described in which researchers support victim engagement in peer research to catalyze a social movement of victims in post-conflict Nepal. Résumé: La justice transitionnelle vise à résoudre les problèmes passés de violence accompagnant les transitions politiques hors de régimes autoritaires et de conflits armés. Issue d'un discours mondial prescriptif, la justice transitionnelle est souvent étrangère aux contextes dans lesquels elle est appliquée et aux populations qu'elle est censée servir. La justice transitionnelle est souvent ancrée dans une approche libérale téléologique à la transition dont l'aboutissement est censé être une démocratie libérale. Les analyses critiques de la justice transitionnelle ont appliqué des méthodologies qualitatives pour connaître les vraies aspirations de ceux que la justice transitionnelle met de l'avant—notamment les victimes de violence—et pour démontrer que les mécanismes de justice transitionnelle servent les visées des élites tout en écartant la participation des populations socialement marginalisées. Une autre méthode, sous-employée, d'obtenir la participation des victimes, est de mobiliser les victimes et organisations de défense des victimes, une approche émancipatoire qui vise à donner aux victimes leur propre champ de participation aux débats de justice transitionnelle. Dans cet article, l'on décrit une initiative de recherche auprès d'une organisation de victimes fondée sur le modèle Participatory Action Research (« Recherche d'action participative ») dans laquelle les chercheurs encouragent la participation des victimes dans la recherche auprès de leurs pairs en vue de catalyser le mouvement social des victimes au Népal post-conflictuel.